2019
DOI: 10.1016/j.ssresearch.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Spousal migration and married adults’ psychological distress in rural China: The roles of intimacy, autonomy and responsibility

Abstract: Spousal separation due to migration is a prevalent phenomenon in the developing world, but its psychological consequences for left-behind partners are largely understudied. Using data from 2010, 2012 and 2014 China Family Panel Studies (CFPS), this paper first examined whether spousal migration causes rural married adults any psychological distress; this finding was then advanced by testing the mechanisms that could potentially explain the linkage between these two variables. Inverse Probability Weighting (IPW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Our findings are consistent with a recent study in India, reporting women's increased responsibilities in agricultural work, water fetching, and child care after husbands' migration and a negative consequence for women's food security, a risk factor for poor health ( Choithani, 2020 ). Another study in China also found a detrimental effect of husbands' migration on women's mental health through women's added responsibility of being the household master ( Tong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with a recent study in India, reporting women's increased responsibilities in agricultural work, water fetching, and child care after husbands' migration and a negative consequence for women's food security, a risk factor for poor health ( Choithani, 2020 ). Another study in China also found a detrimental effect of husbands' migration on women's mental health through women's added responsibility of being the household master ( Tong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a patriarchal society, men usually act as the household head and take responsibilities for managing household affairs, family business, and agricultural production. In the husbands' absence, the wives undertake more responsibilities in farming, family business, household management, and child-rearing ( De Snyder, 1993 ; Mu and Van de Walle, 2011 ; Paris et al, 2005 ; Tong et al, 2019 ). For instance, in rice-producing villages of Uttar Pradesh, India, women undertook a broader range of farm tasks and a heavier workload to compensate for the absence of migrant husbands’ farm labor ( Paris et al 2005 ).…”
Section: Theory and Literaturementioning
confidence: 99%
“…Those who choose to remain single and live alone may not face many negative consequences of living alone (Ho 2015;Raymo 2015), and the rise of solo living for them could be seen as reflecting an increased individualism. In contrast, migrants who leave their families behind to work and live alone in cities may be more negatively affected (Gu, Feng, and Yeung 2018;Tong, Chen, and Shu 2019). Results in this study underscore the importance of internal migration flows in shaping the high concentration of one-person households in the most developed areas in China.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast to the findings of Klinenberg (2012) and other recent studies, our findings suggest that living alone in highly developed areas in China is largely a temporary, transitory arrangement for working-class migrants in that period. Despite its temporary nature, this living arrangement may have adverse long-term effects on migrants' family relations and individual well-being (Mu and Yeung 2020;Tong, Chen, and Shu 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Family intimacy refers to the emotional connection between family members ( Luo et al, 2020 ). Family intimacy can rebalance the family decision-making power and support the autonomy of family members ( Tong et al, 2019 ). It can reduce family conflict and psychological maladjustment, depression, and emotional disturbance at the individual level.…”
Section: Theoretical Backgroundmentioning
confidence: 99%